Evaluation of store lesion in platelet obtained by apheresis compared to platelet derived from whole blood and its impact on the in vitro functionality. Issue 3 (December 2015) - Quintero, M.; Núñez, M.; Mellado, S.; Maldonado, M.; Wehinger, S.
Abstract: Platelet units for transfusion purposes are obtained manually from whole blood or by apheresis, in an automated process. In both methods, platelets during storage present a characteristics grouped under the name "storage lesion" that are associated with adverse effects on platelet units. Oxidative stress has been claimed to be one of major causes, leading to activation and apoptosis processes affecting their post transfusion functionality. In this work, we observed an association between apheresis and a reduced presence of oxidative stress and better results in functional markers in stored platelets, compared to manually obtained platelets. Then, apheresis which would ensure a greater number of functional platelets during the 5 days of storage, compared to concentrates obtained from whole blood.